IMPORTANCE OF DAMAGE OF THE HEART IN PATIENTS WITH RHEUMATOID ARTHRITIS - Mukhammadieva S. M. (Modern American Journals, 2025)
We were investigated 102 patients with rheumatoid arthritis (RA). Research results demonstrated that cardiac pathology has flowed latent and subclinical in this patient’s category, i.e. clinical changes by heart was minimal and rarely become on the first place in general view of the disease. In these patients more often, we found infringements morph-functional indexes’ on the left part of the heart, diastolic function of the left ventricle, what pointed to no adaptive character modeling left part of the heart.
Keywords: Rheumatoid arthritis, cardiovascular system, diagnostics.